АЛИШЕР НАВОИЙ ИЖОДИДА ТАРИХИЙ ҲАҚИҚАТ ВА БАДИИЙ ТЎҚИМА (Scientific journal of the Fergana State University, 2023)
The article considers artistic interpretation of historical information of A.Navoiy’s creative work in “Hamsa”.